Trimming, Miniaturization and Ideality via Convolution Technique of TRIZ A Guide to Lean and High-level Inventive Design - Kwatra, Saurabh; Salamatov, Yuri.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2013)
The book is a valuable research tool-kit for innovators, amateur & professionals alike. Additionally, College & University faculties on Engineering, who organize yearly workshops internationally will find hundreds of novel themes to choose from. Some teachers might just secretly buy this book to introduce out-of-box brain-teasers in classroom to add fizz to normal (at times boring) lecturing. The book can be used as main/add-on textbook towards following courses: (1) Master's degree programs on design innovation worldwide and (2) Senior undergraduate courses in industrial, engineering & product design.
Foreword by Professor K Munshi -- Preface -- Laws of Technical Systems’ Evolution -- Origins of Convolution -- Idealization and Convolution: two sides of same coin?.- Four types of Convolution; Miniaturization embedded in 2nd type -- General scheme of TS evolution in history of technology -- Convolution and Trimming via Convolution.
Keywords: Engineering design; Industrial design; Machinery; Philosophy; Engineering Design; Industrial Design; Machinery and Machine Elements; Philosophy of Technology